REAKSI PASAR MODAL PADA KELOMPOK USAHA ERICK THOHIR: SEBELUM DAN SESUDAH AKUISISI PHILADELPHIA 76ERS, DC UNITED, DAN INTERNAZIONALE MILANO - Brillian Wicaksana (Master of Accounting Universitas Trunojoyo Madura, 2013)
Erick Thohir is one kind of typhoon were his action in acquisition world sport club were outrageus. The purpose of this research was to analyzethe differences of stock price and stock trading volume activity pre and post of acquisition information on spor club, so that investors could use this event to gain benefit. This research used eventstudy method to observe average stock price, and trading volume activity within fivedays, amonth and three month pre and post event date. This research used secondary data collected from Yahoo Finance. The data used in research was taken from : A Year announcement date of acquisition information applied as event date (to), daily closing price, theamount of daily traded share and the amount of listed share. There were 4 companies below TNT group which list on Indonesia Stock Exchange.Results of the study showed that there weresignificant differences of stock price only in Basket Ball club acquisition from pre and post event. Football Club were not giving any difference on stock and trading volume during the period.